An instrument to evaluate nightmares, bad dreams and alternating personalities in individuals with craniomandibular disorders (CMDS) and bruxing behavor (BB) - molina, omar franklin franklin (Cadernos UniFOA, 2016)
Objectives: Review the literature on nightmares and develop a questionnaire on nightmares to be used in individuals presenting craniomandibular disorders and bruxism. Material and Methods: Review of 50 papers related to dissociation, nightmares, bad dreams, bruxism and temporomandibular disorders. Results: A questionnaire with 100 questions related to 15 categories of dreams, bad dreams and nightmares was developed. Violence, rage, aggression, pursuit, sexuality, animals, persecution, critics, voices criticizing or instigating to use violence and commit suicide; shame, sexual aggression and different types of abuse were the most common themes reported in the reviewed literature. Conclusions: A questionnaire to assess dreams, bad dreams and nightmares would be a useful instrument to be used in individuals presenting bruxism and craniomandibular disorders. The instrument covers most of the issues mentioned in the literature, and another advantage is that it could be used for the evaluation of alternating entities or ego states.